THE ROLE OF AGE IN THE INCIDENCE OF POSTOPERATIVE DELIRIUM IN UROLOGY - Gani, Haxhire; Beqiri, Vjollca; Domi, Rudin; Naco, Majlinda; Hoxha, Bilbil; Janko, Aurel; Shkembi, Pranvera (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2016)
The aim of the study was to investigate the role of age in the incidence of postoperative delirium (POD) in urology. Material and methods: The patients were up to 65 years old. After preoperative informed written consent, the enro lled subjects had baseline cognitive and functional assessments. Postoperatively, subjects were assessed daily for delirium using the confusion assessment method. The effectiveness of routine screening of postoperative delirium in the elderly using the Confusion Assessment Method (CAM). Psychiatrists are not necessary in this case. Results: The study design was prospective and descriptive. During the study period, 1496 patients were enrolled before urology operations. All patients that were admitted in the urology clinic were over 65 years old (1496 patients). The study period was from January 2010 to December 2012. Patients that had been diagnosed and treated for psychiatric problems (Alzheimer痴, senile dementia, schizophrenia) were excluded from the study. All patients were routinely preoperative analysed and were then analysed to determent which factor had a greater effect and which had no effect on those complications. The overall incidence of delirium was 18% (270/1496). Conclusions : In the current study, delirium occurred in 18% of the elderly patients after urology operations, and the incidence of delirium was higher in male patients. Several preoperative variables were associated with an increased risk of delirium including older age (χ2 for trend = 14.3; p < 0.01).